Adsorção de fenol por biocarvão de Eucalyptus saligna ativado com NiCl2.6H2O - Mesquita, Mateus da Silva (2023)
The treatment of formation water still represents one of the greatest challenges in the oil industry. Among the various pollutants found in produced water, phenol is of particular concern, due to its high toxicity. The aim of this work was to synthesize a Eucalyptus saligna sawdust biochar activated with NiCl2 in fixed bed slow pyrolysis, followed by evaluation of its capacity for the adsorption of phenol. When comparing the results of chemically activated adsorbent with a pristine adsorbent, the higher efficiency in phenol removal was observed with biochar activated with NiCl2. The noteworthy widening of pores on average and the acquisition of new and/or intensified functional groups (mostly containing O) justified the enhanced adsorption. Both adsorbents were characterized using scanning electron microscopy, energy dispersive spectroscopy, Fourier transform infrared spectroscopy, powder X-ray diffractometry, nitrogen porosimetry using the Brunauer-Emmett-Teller and Barrett, Joyner e Halenda method. The adsorption capacity of the activated biochar with NiCl2 varied slightly (Q=21 a 21.4 mg.g-1 ) at different pH of the phenolic solution (2 to 9). The ideal dosage of biochar obtained was 1 g.L-1 . The adsorption kinetics could be fitted using the Elovich model (R²adj.=0.99, MRE=2.412%), suggesting the attainment of equilibrium at 240 minutes through chemical adsorption on a heterogeneous (irregular) surface. The adsorption isotherms confirmed that multiple layers of the adsorbent were involved in phenol removal, justified by the excellent fits of the Redlich-Peterson (R²adj.=0.998, MRE=1.46%) and Freundlich models (R²adj.=0.995, MRE=3.74%). The maximum adsorption capacity of the activated biochar with NiCl2 obtained was 76.65 mg.g-1 (C0=200mg.L-1 ). Furthermore, thermodynamic evaluation indicated that the adsorption was exothermic (ΔH⁰=-54.71 kJ.mol-1 ), spontaneous (∆G 0=-33.51 kJ.mol-1 ), ordered (ΔS 0=-0.07 kJ.mol-1K -1 ), justified by the Van’t Hoff equation with dimensionless Ke 0 (Redlich-Peterson: R²adj.=0.859). Interestingly, physical interaction mechanisms predominated during thermodynamics. Therefore, a two-stage adsorption system was suggested (1st: physical 'Van der Waals forces' and 2nd: chemical ' electron donor-acceptor complex'). The study of ionic strength was also conducted, varying NaCl from 0 to 1000 mM in solution, with no significant interferences observed. Finally, desorption experiments were carried out through thermal treatment in an inert atmosphere. After three regeneration cycles, the efficiency remained close to 70%. Regeneration through eluents was not efficient, possibly due to the strong chemical bonds between the adsorbent and the adsorbate.